2003
DOI: 10.1097/00004850-200305000-00004
|View full text |Cite
|
Sign up to set email alerts
|

Precautionary measures reduce risk of definite neuroleptic malignant syndrome in newly typical neuroleptic-treated schizophrenia inpatients

Abstract: Neuroleptic malignant syndrome (NMS) is a potentially lethal antipsychotic drug (APD)-induced thermoregulatory disturbance. We hypothesized that several precautionary measures taken after administeration of APDs might prevent progression to definite NMS. The study group included 657 consecutively admitted drug-free schizophrenia inpatients who received various typical APDs for 28 days. Specific predefined precautionary measures were employed for this group. The comparison group (n=192) consisted of typical APD… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2004
2004
2015
2015

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 10 publications
0
4
0
Order By: Relevance
“…Once antipsychotics are stopped, NMS is self-limited barring complications, with the duration to resolution of NMS up to two weeks in the majority of cases (Shalev & Munitz, 1986;Addonizio et al, 1987;Caroff et al, 1988). The notion that prompt withdrawal of the offending agent at early stage can prevent progression to definite NMS has been corroborated by the study reported by Shiloh et al (2003).…”
Section: Clinical Course and Outcomementioning
confidence: 71%
See 1 more Smart Citation
“…Once antipsychotics are stopped, NMS is self-limited barring complications, with the duration to resolution of NMS up to two weeks in the majority of cases (Shalev & Munitz, 1986;Addonizio et al, 1987;Caroff et al, 1988). The notion that prompt withdrawal of the offending agent at early stage can prevent progression to definite NMS has been corroborated by the study reported by Shiloh et al (2003).…”
Section: Clinical Course and Outcomementioning
confidence: 71%
“…The high incidence of NMS reported in earlier studies from the United States is, however, evidently overestimated due to a variety of factors, e.g., retrospective study design, loose diagnostic criteria, adherence to an amorphous "spectrum concept", and clinical practices in vogue (Adityanjee et al, 1999a). Based on the more recent reports (Spivak et al, 2000;Montoya et al, 2003;Shiloh et al, 2003) as well as my own clinical experience as a psychiatrist at the front for almost three decades, the incidence of definite NMS does not appear to exceed 2-3 cases out of one thousand consecutive patients treated with antipsychotics, as long as precautionary measures and monitoring are cautiously and sufficiently employed for the early recognition and prevention of NMS.…”
Section: Epidemiologymentioning
confidence: 99%
“…proper hydration and nutrition in neuroleptictreated patients, low-potency neuroleptics), obtaining and analyzing detailed history of previous episodes, and monitoring of early signs of NMS. The physician should wait approximately two weeks after recovery from NMS before introducing neuroleptics again in the patients [4,31]. Furthermore, a written informed consent should be obtained from patients and family members regarding the risks and benefits of restarting antipsychotic treatment.…”
Section: Treatment the Success In Nms Treatment Depends On Prompt DImentioning
confidence: 99%
“…9,10 We note that some investigators are examining ways to identify NMS early and even prevent NMS. 9,11 We also hope to examine some of the other risk factors listed above, such as low baseline serum iron level. The study of NMS is difficult due to the paucity of prospective studies.…”
Section: Sirmentioning
confidence: 99%